The Need for the Islamization of Knowledge in Accounting - Jamaluddin Majid; Safri Haliding (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
The Need For The Islamization of Knowledge In Accounting. This article tries to analyze the term “Islamization of knowledge method through accountancy. The economic system and the foundation of philosophy its system may influence the accounting practice that Islamic worldview provides the original source of revelation in a Muslim society by using Islamic literally of being the adherents to Islam due to be vicegerents of god and providing accountability in all aspects. Islam as a way of life, covering all activities and economic activities as accounting as well are only small part of Islam, through Al Quran and Al Hadits. In terms of developing of Islamic accounting system that as social science and institution may provide a way to satisfy its social economic objective in order to meet the benefit in this world and hereafter.  DOI: 10.15408/aiq.v6i1.1366